Rancang Bangun Aplikasi Manajemen Keuangan di Pondok Pesantren Miftahul Hidayah Berbasis Web - Yoga Handoko Agustin; Sri Rahayu; Yusuf Abdul Fatah (Jurnal Algoritma, 2023)
Financial management is an activity of managing finances, where this financial management is managed by the management of the Islamic boarding school which will then be reported to the treasurer of the Foundation. Islamic Boarding School Financial Management is an institutional activity related to the payment of monthly student contributions, meals, electricity, cash and charity or infaq money either from the parents of the students or from the congregation of the miftahul hidayah Islamic boarding school. Financial management carried out by Islamic boarding school administrators often results in errors in data collection due to human error and produces inaccurate data both expenditure and income. Based on these problems, a financial management application was designed at the Miftahul Hidayah Islamic boarding school using the PHP programming language with a MySQL database and using the Rapid Application Development (RAD) methodology, the stages of which used Requirement Planning, RAD Design Workshop and Implementation. Then use the Data Flow diagram (DFD) modeling. The results of this study are in the form of financial management applications with several features such as student data, financial balances, weekly reports, monthly reports and annual reports.